Pulse pressure amplification and aortic augmentation index in adolescent competitive handball players - Potora, C. S.; Albu, A.; Tache, S. (Medicina dello Sport, 2017)
BACKGROUND: Central hemodynamics and characteristics of wave reflexion are important determinants of left ventricular afterload. A decrease in central pulsatile flow might be associated with a reduction in left ventricular load and favorable cardiovascular effects. There are few studies which investigated the potential favorable role of intensive training on central hemodynamics. The aim of this study was to evaluate pulse pressure (PP) amplification and aortic augmentation index (Aix), as parameters of central hemodynamics and wave flection, in adolescent handball athletes. METHODS: Central aortic blood pressures, aortic Aix and brachial blood pressures, were measured using an oscillometric device, in twenty four adolescent handball athletes (mean age 16.4±0.1) and seventeen healthy controls, matched for sex, age and height. We calculated PP amplification as the ratio between brachial PP and aortic PP. Cardiorespiratory fitness was determined by the estimation of maximal oxygen consumption (VO2max). RESULTS: The PP amplification was significantly higher (1.70±0.35 vs. 1.58±0.29, P=0.01) in athletes compared to controls, whereas aortic Aix and aortic Aix75 were significantly lower in handball payers compared to controls (-0.57±0.62 vs. 5.45±2.6, P=0.01 and -1.9±0.9 vs. 4±3.1, P=0.03, respectively). The intensity of cardiovascular fitness correlated directly with PP amplification and inversely with aortic Aix. CONCLUSIONS: Long-term, intensive training may have favorable effects on central hemodynamics, in adolescent handball athletes, suggesting a positive effect of exercise on wave reflection. This hemodynamic profile may protect cardiovascular system in young athletes.